(untitled) (Bulletin of criminological association of Ukraine, 2023)
In order to provide answers to many broad issues of the pre-trial report, we have analyzed a large number of scientific positions devoted to this issue, namely, more than 50 scientific professional articles by Ukrainian authors. The focus is on the most important/problematic aspects that may be useful for a comprehensive understanding of this topic in order to develop constructivist/normativist management decisions. Today, criminological science and criminal procedural law are developing at an innovative pace and are acquiring new modifications due to the interdisciplinary/interdisciplinary paradigm, one of the important conditions of which is pre-trial probation and its manifestation and result - a pre-trial report as an important recommendation for making a final decision in a case, namely, rendering an accurate, clear, accessible, constructive and fair verdict - a sentence. Conducting a significant ideological, generalizing, analytical work "according to the Lombroso method with 26 thousand criminals" in terms of the spiritual and value characteristics of each individual is an important task today. It is about getting ahead of crime processes, making it impossible/reducing the number of pre-trial reports and, as a result, making such a report in the shortest possible time. In essence, this is work when relevant information is available to everyone through the proper work of educators/teachers, psychologists, juvenile prevention, the entire police corps/state apparatus due to a properly structured policy in the scientific and practical sphere, etc. An important problem is that most theorists and practitioners, as well as the law enforcement and administrative apparatus in general, are rather skeptical about the problem of drawing up a pre-trial report. In this regard, it is necessary to transform the consciousness of practitioners, especially judges, in the direction of ensuring maximum individualization of criminal punishment and development/adoption of the most optimal legal decision in the case.